Uji Kualitas dan Identifikasi Sabun Padat Komersial Berbasis Lemak Hewan Menggunakan FTIR - Pradini, Ni Komang Virginia; Salamah, Nina; Guntarti , Any; Nurkhasanah , Nurkhasanah (Journal of Pharmaceutical and Sciences, 2026)
Background: Solid soap is produced by saponification of fatty acids with strong bases, and its quality is influenced by the type of fat used. Objective: This study aims to evaluate the physical and chemical quality of solid soap made from beef tallow and lard and to identify compound profiles using Fourier Transform Infrared Spectroscopy (FTIR). Method: The methods include dry-rendering fat extraction, solid soap formulation, and soap quality tests (organoleptic properties, pH, moisture content, and foam height). FTIR analysis was conducted to compare the absorption spectra of each soap. Results: The results showed that soaps derived from both fat sources met all quality requirements specified in the Indonesian National Standard (SNI). FTIR analysis revealed generally similar spectral patterns; the lard solid soap exhibited a characteristic absorption band at approximately 3009 cm⁻¹, corresponding to =C-H stretching vibrations of unsaturated fatty acids. In contrast, this band was not detected in the solid soap made from beef tallow. In addition, the CH₂ rocking vibration around 720 cm⁻¹ was more pronounced in the beef tallow solid soap, indicating a higher proportion of long-chain saturated fatty acids. Conclusion: FTIR effectively identifies fat types and can be used in raw material authentication, especially in product halalness.